2020
DOI: 10.3390/cancers12040786
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for the Tumor Suppressor Gene ITF2 in Tumorigenesis and Chemotherapy Response

Abstract: Despite often leading to platinum resistance, platinum-based chemotherapy continues to be the standard treatment for many epithelial tumors. In this study we analyzed and validated the cytogenetic alterations that arise after treatment in four lung and ovarian paired cisplatin-sensitive/resistant cell lines by 1-million microarray-based comparative genomic hybridization (array-CGH) and qRT-PCR methodologies. RNA-sequencing, functional transfection assays, and gene-pathway activity analysis were used to identif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Previously clinic research suggested that HOXD9 level was highly expressed in the cancerous tissues from NSCLC patients [15]. This means that high HOXD9 expression might be associated with the development of NSCLC.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previously clinic research suggested that HOXD9 level was highly expressed in the cancerous tissues from NSCLC patients [15]. This means that high HOXD9 expression might be associated with the development of NSCLC.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, HOXD9 silencing induced apoptosis of tumor cells by activating the p53 pathway [9]. Recently, HOXD9 was found to be highly expressed in tumor samples from NSCLC patients and had a significant negative correlation with patients' overall survival [15]. Therefore, HOXD9 is proposed to be a valuable prognostic biomarker for NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…These cell lines were purchased from the ATCC (Manassas, VA, USA) or ECACC (Sigma-Aldrich, Spain) and authenticated by the Genomics Department of the Alberto Sols Biomedical Research Institute (iiBm) CSIC-UAM, through microsatellite analysis of speci c loci within the Human Genome using the GenePrint 10 kit (Promega, USA) (Supplementary Table 1). Cisplatin (CDDP) resistant variants H23R, OVCAR-3R and A2780R were established previously by our group (41,(71)(72)(73)(74). Carboplatin (CBDCA) resistant subtypes H23 and A2780 were established by exposing cells to increasing doses of carboplatin as described in the literature (74), obtaining a nal CBDCA concentration of 2.5 and 1.25 µg/mL, respectively (Supplementary Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…TCF4 exerts oncogenic effects by promoting the proliferation, invasion, and chemoresistance of melanoma, lung, colorectal, and breast cancers [ 16 , 22 , 23 , 24 , 25 , 26 ]. In contrast, several studies have demonstrated that TCF4 suppresses the growth and progression, which are associated with poor prognosis, of non-small cell lung carcinoma and colorectal cancer [ 27 , 28 , 29 , 30 ]. TWIST1, a bHLH-domain-containing transcription factor, is reported to promote epithelial-to-mesenchymal transition (EMT), which increases the invasiveness and metastasis of epithelial cancers [ 31 ].…”
Section: Introductionmentioning
confidence: 99%